Bilateral cochlear nerve absence in a 3 year old child with VACTERL association. (February 2017) - Rudić, Milan; Wong, Winson; Viner, Stuart; Strachan, David; Raine, Christopher
Abstract: We report a case of a 3 year old boy with bilateral profound sensorineural hearing loss diagnosed from New Born Hearing Screening, with severe form of VACTERL association. He was referred to our Cochlear Implant Unit for assessment with regard to the possibility of cochlear implantation. MRI findings have showed bilateral vestibulocochlear cystic abnormalities. Only single nerve noted within the IAM on the right and likely single nerve within the IAM on the left. Hence, decision was made not to offer cochlear implantation. This is the first report of severe bilateral cochleovestibular nerve abnormalities to be associated with VACTERL.